Human Rights and The New Order Regime; A Critical Discourse Analysis Towards The Novel “Laut Bercerita” - Erika Nofia Pransisca Permatasari; Wiwi Widiastuti; Faisal Fadilla Noorikhsan (International Journal of Social Sciences Review, 2021)
The purpose of this research was to analyze, compare, and reconstruct the reality of human rights abuses in the last decade of the new order. Prior to the collapse of the New Order dictatorship, there were anomalies in the kidnapping and forced disappearance of student activists. The analysis of literary works in the form of novels becomes the subject of inquiry in order to see the specifics of human rights abuses that occur as a result of power practices. The study employs state power theory and human rights conventions in order to develop new knowledge for authors and readers through the application of a critical paradigm with three levels of examination. The author used a descriptive research approach in this study, which involves analyzing conversation using the Norman Fairclough model. Manuscript documents were used to collect data, which was subsequently examined using reading and note-taking procedures. Novels, as literary works, can disclose details of an event that are not adequately described in news reports; in this situation, literary works such as novels can also serve as an alternate channel for conveying event critique. The novel "Laut Bercepat" was examined using the analytical technique to determine how the New Order was depicted, the link between the state and society, and how the New Order was identified. Human rights abuses are attempts to keep power under the guise of national security and order.